ANALISIS ISI KUANTITATIF AKUN INSTAGRAM @DIVISIHUMASPOLRI DALAM MEMBANGUN KEPERCAYAAN PUBLIK - Yudananto, Erik; Damastuti, Riski (POPULIKA, 2023)
Building public trust in the current era is something that is commonly done by agencies. One of the goals of building public trust is to improve performance and also to achieve the goals of an organization or agency. In the last few months, Polri has experienced a decline in public trust as a result of several cases involving several individuals. One of the efforts to build public trust by the Police is through social media uploads @divisihumaspolri. This study discusses quantitative content analysis of Instagram @divisihumaspolri content in building public trust, using a quantitative approach and using quantitative content analysis methods. The purpose of this study is to find out what elements of trust are used by Polri's public relations in uploads to the Instagram account @divisihumaspolri. The indicators used in this theory use the concept of The Trust Radar. The indicators used to build public trust based on The Trust Radar consist of empathy, transparency, expertise, and commitment. Based on the results obtained, it can be seen that the Instagram account @divisihumaspolri uses a lot of content in the form of videos rather than using photo content, as well as using elements of commitment in building public trust. Keywords: Polri; Public Relations; Instagram; Public trust.